2004
DOI: 10.1081/prg-200030345
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C for Assessment of Glomerular Filtration Rate in Hypertensive Disorders of Pregnancy

Abstract: Serum cystatin C seems to reflect glomerular filtration rate reliably in hypertensive pregnant women and avoids the inaccuracy associated with the 24-hour urine collection, which is time consuming and subject to improper collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…During pregnancy, there is a loss of this negative charge, which results in a reduced filtration of the positively charged cystatin C. This effect is likely to raise serum cystatin C levels. [18][19][20][21] Till now, the results in pregnancy for GFR estimated by cystatin C are conflicting. [19][20][21] It is conceivable that the accuracy of the GFR estimation in pregnancy may improve by combining serum cystatin C and creatinine in a single equation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, there is a loss of this negative charge, which results in a reduced filtration of the positively charged cystatin C. This effect is likely to raise serum cystatin C levels. [18][19][20][21] Till now, the results in pregnancy for GFR estimated by cystatin C are conflicting. [19][20][21] It is conceivable that the accuracy of the GFR estimation in pregnancy may improve by combining serum cystatin C and creatinine in a single equation.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Till now, the results in pregnancy for GFR estimated by cystatin C are conflicting. [19][20][21] It is conceivable that the accuracy of the GFR estimation in pregnancy may improve by combining serum cystatin C and creatinine in a single equation. 22 In conclusion, our data confirm 2 previous reports on the underestimation and limited accuracy of the Cockroft-Gault and MDRD formulas in estimating GFR in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Because no prior studies of renal function have been reported under the conditions imposed by this protocol, blinded CrCl data were reviewed prior to analysis for possible outliers. Based on the range of published results of CrCl in normal pregnancy and PE, 20,21 aberrant CrCl values were identified for 10 time points in a total of seven subjects (range: 354 to 1082 mL/min). Six (three DIF, three placebo) of these time points were at baseline with short collection times (120 to 240 minutes) and high urine flows (1.75 to 14.4 mL/min), conditions that would promote spuriously high values.…”
Section: Methodsmentioning
confidence: 99%
“…Preeclampsia manifests by proteinuria, hypertension, and impaired renal function 83 . Assessment of renal function is important in the evaluation of the pregnant hypertensive patient 1 . Serum Cystatin C seems to reflect glomerular filtration rate reliably in hypertensive pregnant women and avoids the inaccuracy associated with the 24-hour urine collection, which is time consuming and subject to improper collection 1 .To determine the cutoff point of Cystatin C for the detection of renal impairment in hypertensive pregnancies.…”
Section: Copernicus Publishingmentioning
confidence: 99%